2021
DOI: 10.1115/1.4049789
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Journal Bearing Induced Nonlinear Rotordynamic Vibrations

Abstract: Nonlinear elements found in fluid film journal bearings and their surrounding structures are known to induce sub- and super-synchronous, chaos and thermally-induced instability responses in rotor-bearing systems. The current review summarizes the literature on journal bearing induced nonlinear, rotordynamic forces and responses. Nonlinear, thermo-elasto-hydro-dynamic (TEHD) aspects of journal bearings has become increasingly important in high performance turbomachines. These have significant influence on beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…The results showed that friction-induced system vibrations were caused by the coupling effects of interface nonlinear friction and system components [266]. The role of nonlinear coupling models in the study of friction vibration of WLBs is becoming more and more important [267]. Therefore, theoretical research must establish and solve the coupling models according to the actual influencing factors by considering the hydrodynamic effect, thermal effect, and the deformation effect of the bearing and shaft.…”
Section: Frictionmentioning
confidence: 99%
“…The results showed that friction-induced system vibrations were caused by the coupling effects of interface nonlinear friction and system components [266]. The role of nonlinear coupling models in the study of friction vibration of WLBs is becoming more and more important [267]. Therefore, theoretical research must establish and solve the coupling models according to the actual influencing factors by considering the hydrodynamic effect, thermal effect, and the deformation effect of the bearing and shaft.…”
Section: Frictionmentioning
confidence: 99%
“…Jamil et al 20 investigated the impact of wear in journal bearings on the dynamic behaviour of rotor bearing system relying upon the derivation of dynamic stiffness and damping coefficients of worn journal bearing. Kim et al 21 presented a review that summarized the previous studies done on journal bearing induced nonlinear, rotordynamic forces, and responses. Viana et al 6 investigated the boundaries for linear approximation of the hydrodynamic forces present in lobed hydrodynamic bearings in highly loaded operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the load capacity performance of hydrostatic bearings has consistently been a focal point of research [6]. Wang et al [7] adopted a new method to determine the oil chamber pressure of sliding bearings.…”
Section: Introductionmentioning
confidence: 99%